2023
DOI: 10.3389/fsurg.2023.1107461
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Endoscopic closure with double stenting and autologous fascia lata graft of large tracheo-esophageal fistula

Abstract: IntroductionRadiotherapy and esophageal stenting are usually employed to manage esophageal localization of distant cancer. However, they are also related to the occurrence of an increased risk of tracheoesophageal fistula. Tracheoesophageal fistula management in these patients involves dealing with poor general conditions and short-term prognosis. This paper presents the first case in literature of bronchoscopic fistula closure through an autologous fascia lata graft placement between two stents.Case report an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Currently, endoscopic intervention has been considered as the most effective method for palliation of malignant ERF ( 6 ). There are several research reported on the endoscopic treatment of malignant ERF, including airway stents, esophageal stents, double stents, and autologous tissue ( 15 , 16 ). European Society of Gastrointestinal Endoscopy (ESGE) Guideline recommends the application of double stenting (esophagus and airway) when fistula occlusion is not achieved by esophageal or airway prosthesis placement alone ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, endoscopic intervention has been considered as the most effective method for palliation of malignant ERF ( 6 ). There are several research reported on the endoscopic treatment of malignant ERF, including airway stents, esophageal stents, double stents, and autologous tissue ( 15 , 16 ). European Society of Gastrointestinal Endoscopy (ESGE) Guideline recommends the application of double stenting (esophagus and airway) when fistula occlusion is not achieved by esophageal or airway prosthesis placement alone ( 17 ).…”
Section: Discussionmentioning
confidence: 99%